Does dog-ownership influence seasonal patterns of neighbourhood-based walking among adults? A longitudinal study - Rock Melanie; McCormack Gavin R; Lail Parabhdeep (BMC, 2011)
Abstract Background In general dog-owners are more physically active than non-owners, however; it is not known whether dog-ownership can influence seasonal fluctuations in physical activity. This study examines whether dog-ownership influences summer and winter patterns of neighbourhood-based walking among adults living in Calgary, Canada. Methods A cohort of adults, randomly sampled from the Calgary metropolitan area, completed postal surveys in winter and summer 2008. Both winter and summer versions of the survey included questions on dog-ownership, walking for recreation, and walking for transportation in residential neighbourhoods. Participation in neighbourhood-based walking was compared, among dog-owners and non-owners, and in summer and winter, using general linear modeling. Stability of participation in neighbourhood-based walking across summer and winter among dog-owners and non-owners was also assessed, using logistic regression. Results A total of 428 participants participated in the study, of whom 115 indicated owning dogs at the time of both surveys. Dog-owners reported more walking for recreation in their neighbourhoods than did non-owners, both in summer and in winter. Dog-owners were also more likely than non-owners to report participation in walking for recreation in their neighbourhoods, in summer as well as in winter. Dog-owners and non-owners did not differ in the amount of walking that they reported for transportation, either in summer or in winter. Conclusions By acting as cues for physical activity, dogs may help their owners remain active across seasons. Policies and programs related to dog-ownership and dog-walking, such as dog-supportive housing and dog-supportive parks, may assist in enhancing population health by promoting physical activity.